Search and collection of Yamato meteorites in the 1982-83 field season,Antarctica - Katsushima, Takayoshi; Nishio, Fumihiko; Ohmae, Hirokazu; Ishikawa, Masao; Takahashi, Shuhei (1984)
P(論文) Search and collection of Antarctic meteorites were carried out by the inland traverse party of the 23rd Japanese Antarctic Research Expedition (JARE-23) in the Meteorite Ice Field near the Yamato Mountains in 1982-83. Collected meteorites (named Yamato-82 meteorites) are 211 specimens, and their total weight is over 35kg. A preliminary study revealed that the Yamato-82 meteorites included 10 carbonaceous chondrites, 5 diogenites, 13 eucrites, 3 unclassified achondrites and a large number of chondrites. Among them, more than 50 specimens were found in the limited area within 1km in diameter, 25km south from Kuwagata Nunatak of the Minami-Yamato Nunataks. Such a meteorite-concentrated area as this one suggests that the sub-ice mountains may exist in the bare ice area and the ice flow carrying meteorites forms a horizontal convergence. departmental bulletin paper